A Novel DCT domain CRT-based watermarking scheme for image authentication surviving JPEG compression - Phua, Jiliang E. (2011)
Digital watermarking techniques have been proposed for copyright protection and authentication of multimedia data. In this paper, we propose a novel Chinese Remainder Theorem (CRT)-based technique for digital watermarking in the Discrete Cosine Transform (DCT) domain that is robust to several common attacks. We compared the performance of the proposed technique with recently proposed Singular Value Decomposition (SVD)-based and spatial CRT-based watermarking schemes. Experimental results have shown that the proposed technique successfully makes the watermark perceptually invisible and has better robustness to common image manipulation techniques such as JPEG compression, brightening and sharpening effects compared to the spatial domain-based CRT scheme. The proposed scheme is able to achieve a Tamper Assessment Function (TAF) value of less than 10% when the watermarked image undergoes JPEG compression between a range of 50 to 70%, where as, the spatial CRT-based scheme produce TAF value of more than 35% and the SVD-based scheme produces TAF value between 10 to 40% depending on the host image, for the same range of compression. When the watermark capacity is doubled, the proposed technique is still able to maintain imperceptibility and low TAF values, for most of the attacks.